2007
DOI: 10.1590/s0100-879x2006005000145
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor necrosis factor-a for the treatment of steroid-refractory acute graft-versus-host disease

Abstract: Allogeneic stem cell transplantation has been increasingly performed for a variety of hematologic diseases. Clinically significant acute graft-versus-host disease (GVHD) occurs in 9 to 50% of patients who receive allogeneic grafts, resulting in high morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…This finding is similar to that observed in inflammatory bowel diseases12, 13 and raises the hypothesis of a specific role of TNF‐α in cibling bowel damage 23. In the context of HSCT, another interesting finding is that the best responses to infliximab were achieved in patients whose GVHD did not involve the liver 3, 16–19. This suggests that infliximab could be particularly interesting for GVHD following liver transplantation.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This finding is similar to that observed in inflammatory bowel diseases12, 13 and raises the hypothesis of a specific role of TNF‐α in cibling bowel damage 23. In the context of HSCT, another interesting finding is that the best responses to infliximab were achieved in patients whose GVHD did not involve the liver 3, 16–19. This suggests that infliximab could be particularly interesting for GVHD following liver transplantation.…”
Section: Discussionsupporting
confidence: 80%
“…In 1992, our center reported for the first time the successful use of home‐made monoclonal anti‐TNF antibodies in refractory GVHD following hematopoietic stem cell transplantation (HSCT) in a pilot study that included 19 patients 15. Since then, various retrospective case series have found encouraging results with infliximab for the treatment of steroid‐refractory acute GVHD following HSCT 3, 16–19. During acute GVHD, TNF‐α is secreted by monocytes and macrophages, leading to donor T cell activation and inducing a cascade of inflammatory cytokine and cell activation and tissue damage 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…recorded in 24% of patients. Other studies in patients with SR aGVHD have reported variable rates of infections, including 83% to 100% (34% to 40% fatal) in patients receiving infliximab [15,36,37], 78% to 100% (8% to 50% fatal) in patients receiving alemtuzumab [14,[38][39][40][41][42], and 67% (12% fatal) in patients receiving etanercept [43]. However, many of those series did not categorize infections by severity.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study assessing the efficacy of infliximab in patients with SR-aGVHD, Couriel et al investigated a cohort of 21 patients and reported an overall response rate (ORR) of 67% [15]. This finding was supported by additional small retrospective studies [16][17][18][19][20][21][22]. A more recent study assessing infliximab salvage therapy in 52 patients reported a complete response (CR) of 15% [23], while a randomized, upfront, phase 3 study comparing infliximab with corticosteroids to corticosteroids alone in aGVHD did not show any benefit [24].…”
Section: Introductionmentioning
confidence: 99%